Etlingera elatior Compounds as Anticancer Agents of Breast Cancer Through Inhibition of Progesterone Receptor: An In Silico Study - Afladhanti, Putri Mahirah; Hamzah, Haidar Ali; Romadhan, Muhammad Despriansyah; Putri, Safa Nabila; Angelica, Ellen Callista; Theodorus, Theodorus (Indonesian Society for Cancer Chemoprevention, 2023)
Breast cancer is the leading cause of cancer-related death in women globally. Progesterone receptor (PR) is known as the prime example of receptors amenable to targeted breast cancer drug therapy. Etlingera elatior is an herbal plant that has been renowned to have anticancer effect. This study aimed to identify the potential compounds derived from Etlingera elatior as anticancer agents of PR in breast cancer using molecular docking method. This study used fifteen compounds from Etlingera elatior along with lonaprisan as the comparative drug. The PR was downloaded from RCSB, whereas compounds and lonaprisan were from Pubchem. The drug-likeness test based on Lipinski’s rule of five was conducted using SwissADME. Toxicity analysis using admetSAR 2.0 was used to predict toxicological profile of the compounds. Compounds and lonaprisan were docked on PR using AutoDock tools 1.5.6 and AutoDock Vina 1.1.2. Molecular interactions were visualized by Discovery Studio v16. A total of nine compounds met the criteria as drugs based on drug-likeness and toxicity tests. All nine compounds except caffeic acid and vanillic acid had higher binding affinities on PR compared with lonaprisan. Ergosterol peroxide exhibited the highest binding affinity on PR with values of -9.8 kcal/mol. Moreover, ergosterol peroxide-PR interaction had thirteen hydrophobic bonds and a hydrogen bond with amino acid residues were found in the active site of PR. Most of the compounds found in Etlingera elatior have the potential to be anticancer agents of PR in breast cancer with ergosterol peroxide being the most potential compound. Further in vitro and in vivo research are needed.Keywords: breast cancer, ergosterol peroxide, Etlingera elatior, progesterone receptor, in silico.